2012
DOI: 10.1111/j.1600-0501.2012.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of implant‐supported over‐dentures retained by double crowns: a practice‐based retrospective study after minimally 10 years follow‐up

Abstract: This study indicates that IODs retained with double crowns offer predictable long-term performance with a limited incidence of biological and technical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 26 publications
7
75
0
Order By: Relevance
“…This was recognized by previous authors (Frisch, Ziebolz & Rinke, 2013; Trullenque‐Eriksson & Guisado‐Moya, 2014) and obvious from the study of Jensen, Meijer, Raghoebar, Kerdijk and Cune (2017). The latter had a mean follow‐up time of 8 years based on implants in function from 3 years up to 16 years of follow‐up.…”
Section: Discussionmentioning
confidence: 52%
“…This was recognized by previous authors (Frisch, Ziebolz & Rinke, 2013; Trullenque‐Eriksson & Guisado‐Moya, 2014) and obvious from the study of Jensen, Meijer, Raghoebar, Kerdijk and Cune (2017). The latter had a mean follow‐up time of 8 years based on implants in function from 3 years up to 16 years of follow‐up.…”
Section: Discussionmentioning
confidence: 52%
“…The cortisol level is widely used in the literature as a varying physiological parameter associated with the presence of stress 29 cases involving the insertion of dental implants and function immediately, i.e., within the same session the patient leaves the dental clinic with prostheses supported by implants, or just with the implant.Naturally, a well-established model in the literature was sought, which led us to choose a chronic-stress model involving physical restraint for 12 hours 11, 13,17,26 . It is currently understood that for successful implant dentistry, certain criteria must be met, including an atraumatic surgical technique, primary stability, implant selection, the quality and quantity of bone 27 , periodic preventive maintenance, and knowledge of the physiological and/ or pathological changes in preexisting conditions 28 . The latter may involve stress.…”
Section: Discussionmentioning
confidence: 99%
“…Seven implants in two patients showed peri-implantitis (prevalence: patient-based = 9.1%/ implant-based = 8%). Five dentures were renewed (prosthetic-survival rate 77.3%) The authors concluded that IODs retained with double crowns offer predictable long-term performance with a limited incidence of biological and technical complications [53].…”
Section: Resultsmentioning
confidence: 99%